Neurodegenrative changes in retina of rats with chronic epileptic syndrome under conditions of treatment with niacin-oxy-ethylidene-phosphonate germanate (MIGU-4) - N. Al-Nadawi; V.I. Kresyun (Ukrainian Society of Ophthalmologists, 2023)
Background: Epilepsy is accompanied by neurodegenerative changes, particularly those in the retina. Elucidation of the mechanisms of retinal alterations in a model of epileptic syndrome may allow for the development of new approaches to pharmacological vision correction. Purpose: To assess the morphological characteristics of the retina, particularly treated with niacin oxy-ethylidene phosphonate germinate (MIGU-4), in the pentylenetetrazole (PTZ)-induced kindling model of chronic epileptic syndrome. Material and Methods: PTZ was administered in Wistar male rats intraperitoneally (i.p.) at a daily dose of 35.0 mg/kg for 21 days. Rats with fully-developed generalized seizures were treated with MIGU-4 ip at a daily dose of 5.0 mg/kg or 25.0 mg/kg for 28 days. Thereafter, the animals were euthanized, their globes were enucleated, and retinal sections were prepared and stained with hematoxylin and eosin for morphological examination. Results: Cell density in the retinal ganglion cell layer was 2.14 times lower, and in the inner nuclear layer and outer nuclear layer, 41.0% and 19.0%, respectively, lower for the rats with fully developed kindled seizures than for controls (р < 0.05). In the presence of treatment with MIGU-4 ip at a daily dose of 25.0 mg/kg, cell density in the retinal ganglion cell layer and in the inner nuclear layer was 38% and 30.5%, respectively, higher than for controls (р < 0.05). There was no significant difference in the cell density in the outer nuclear layer between rats treated with MIGU-4 ip at a daily dose of 5 mg/kg or 25.0 mg/kg and controls (р > 0.05). Conclusion: The PTZ-induced kindling model of chronic epileptic syndrome is accompanied by degenerative changes in the eye. A course of treatment with MIGU-4 causes neuroptotective effects in a model of PTZ-induced retinopathy.